Development of BISAWA (Bingo Aksara Jawa) Media Assisted by Pop Up Book for Teaching Javanese Script Reading to Upper Grade Students - Ma'rifah, Lilik; Insani, Nur Hanifah (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to develop BISAWA (Bingo Aksara Jawa) learning media assisted by Pop Up Book for teaching Javanese script reading to upper grade students. The research method used is Research and Development proposed by Sugiyono through four stages, namely potential problems, data collection, product design, and design validation. Data collection was obtained through interviews and questionnaires, then analyzed using descriptive qualitative and quantitative approaches. Product validation was carried out by material validators to assess learning content and media validators to assess media quality. Based on the results of the material validation test getting a score of 81.3% and the media validation test getting a score of 91.1%, both validators stated that this product is